The insertion/deletion in the DNA-binding region allows the discrimination and subsequent identification of the glucocorticoid receptor 1 (gr1) and gr2 nucleotide sequences in gilthead sea bream (Sparus aurata): Standardizing the gr nomenclature for a better understanding of the stress response in teleost fish species - Vallejos-Vidal, Eva; Khansari, Ali Reza; Teles, Mariana; Reyes-Cerpa, Sebastián; Mancera, Juan Miguel; Tort, Lluis; Reyes-López, Felipe E. (Frontiers in Marine Science, 2022)
Cortisol carries out its physiological mechanism of action through the recognition by the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR) 1 (GR1) and GR2. Previous studies reported that the main difference between gr1 and gr2 nucleotide sequences resides in a 27-nucleotide insertion/deletion in the DNA-binding region, respectively. However, in gilthead sea bream (Sparus aurata) the annotation for gr1 and gr2 seems contradictory. The gr2 sequence possesses the characteristic 27-nucleotide insertion that, in fact, is associated with the gr1 nucleotide sequence. Thus, this study aimed to elucidate the nucleotide sequences for the gr1 and gr2 in gilthead sea bream. The Clustal Omega alignment for different fish species corroborated the presence of such 27-nucleotide insertion/deletion in the DNA-binding region for gr1 and gr2, respectively. Then, we design specific primers set for the amplification of the gilthead sea bream gr1 by polymerase chain reaction (PCR). Importantly, the gr1 nucleotide partial sequence has a high similarity with other gr1 sequences already published for other fish species, being present in all of them the 27-nucleotide insertion in the DNA-binding region. We also detected that in European sea bass the gr1 and gr2 sequences had not been named according to the 27-nucleotide insertion/deletion criteria in the DNA-binding region. Thus, our study makes an urgent call to the scientific community to discuss the establishment of an updated agreement that allows homogenizing the criteria for the nomenclature defining the gr1 and gr2 nucleotide sequences for a better understanding of the stress response in teleost fish species.